Development and early score validation of the Malaysian Educator's Information Technology Attitude Scale (MEITAS) - Wong, Su Luan (Science Publications, 2007)
The purpose of this study was to develop and provide initial validation evidence for an instrument to measure educators’ attitudes toward IT. Data were collected from 817 participants comprising both pre and in-service teachers in four phases. Two separate factor analyses were conducted for the pre-service teacher data and in-service teacher data. Principle component analysis, with varimax rotation, suggested three distinct constructs: affect, perceived usefulness and behaviour. The scores of the instrument also showed high reliability.